Da casa ao macrobordel: o remanescente colonial da escravidão e os (necro)negócios "gore" do Brasil contemporâneo, no romance "pssica" (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2020)
The article proposes a reading of the Brazilian novel Pssica (2015), by Edyr Augusto, starting from the premise that the narrative fictionalizes the problem of sexual exploitation routes in the Brazilian Amazon. The aim of this article is to investigate how trafficking of girls and women in the Amazon is fictionalized, basing itself on the theoretical categories of Necropolítica (Mbembe, 2018); Homo Sacer (Agamben, 2010) and Capitalismo Gore (Triana Valencia, 2010). As a preliminary result of a more detailed study on contemporary Brazilian novels, the novel analysed problematizes life starting from the context of the politics of death, called necropolitics (Mbembe, 2018) by the aesthetic representation of the colonial remnant of slavery and the emergence of criminal markets that flourish among groups subjected to deadly conditions.
Keywords: Brazilian contemporary literature; Amazon; necropolitics; necronarrative; gore capitalism